RADIKALISME AGAMA DALAM PERMAINAN BAHASA: (Perspektif Language Games Ludwig Wittgenstein) - Achmad Bahrur Rozi (Tafhim Al-'Ilmi, 2018)
All religion have different expressions in articulating the truth of their teachings. The differences occur not onlyamongst different religions, but also in school of thoughts, sects, and ideologies in the same religion. Thismeans that the use of religious language amongst the groups is not necessarily lead to one goal and to thesame meaning. This paper aims to examine the use of religious language from the perspective of its usageusing ordinary language philosophy approach (language philosophy) or more specifically known as languagegames intiated by the Austrian-born philosopher Ludwig Josef Johann Wittgenstein (1889). Such study is veryimportant to compenstate for current analysis which tends to be empirical-positivistic. This trend emphasizesthe pragmatic aspects of the language than the grammatical aspect. Thus, in the context of religious language,one the same language of riligous language is used not for one purpose only. This means that there is no onlyone way for religious sentences to gain the meaning, but it can discribe some realities depending on the users.Key Word: Language, Bahasa Agama, Makna AbstrakSemua agama memiliki ekspresi berbeda dalam mengartikulasikan kebenaran ajarannya. Cara pengungkapanyang berbeda ini bahkan tidak hanya terjadi antar-agama yang berbeda, tetapi terjadi juga dalam aliran,mazhab, dan ideology dalam satu agama yang sama. Artinya bahwa penggunaan bahasa agama antarkelompokbelum tentu megarah pada satu sasaran makna yang sama. Tulisan ini bertujuan mengkaji bahasaagama dari perspektif penggunaannya melalui pendekatan filsafat bahasa biasa (language philosophy) ataulebih spesifik dikenal dengan language games yang digagas oleh filsuf kelahiran Austria, Ludwig Josef JohannWittgenstein (1889). Studi semacam ini dipandang sangat penting guna mengimbangi analisis yang selama inicenderung empiris-positivistik. Kecenderungan ini menekankan bahasa pada aspek pragmatic daripada aspekgramatikalnya. Dengan demikian, dapat disimpulkan dalam konteks bahasa agama, bahwa satu bahasa yangsama dari bahasa agama dipakai tidak hanya untuk satu tujuan saja. Ini artinya bahwa pernyataan-pernyataanagama tidak mendapatkan maknanya dengan satu cara saja, tetapi bisa menggambarkan beberapa relaitasmenurut aturan main si pemakainya.Kata Kunci: Language, Bahasa Agama, Makna